Ubique Sunt Leones (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2021)
After the fall of the Tower of Babel, the common human language shattered into a multitude of idioms. However, humankind has never abandoned the desire to rebuild the lost unity: through impositions, by hegemonic civilizations (Greek, Latin, Arabic, Spanish, English); using egalitarian artifices (the Langue Matrice of Descartes or the more recent Esperanto); imagining utopian worlds (Selenian, Sevarite, Laputian). The graphical representation, on the contrary, is only touched by hermeneutical problems. This is true if the mimesis is limited to the outward appearance of an object. If, on the other hand, it is necessary to design what has no visible matter or form, the myth of universal representation crumbles. In 1982, Manfredo Massironi coined the term ‘hypothetigraphy’, defined as an explanatory graphic product of non–visible behaviours, shapes, and structures. Today the main challenge of drawing consists in the representation of phenomena related to the non–visible (economic, social data, regarding tastes and trends, data flows). The field of application of hypothetigraphy has expanded and representation is divided into a myriad of specialized languages. This contribution, leveraging on the notion of hypothetigraphy, analyses some forms of representation trying to distinguish codes based on universal semantic rules from those that adopt specialized languages.
Keywords: hypothetigraphy; representative plate; semantic cluster